Determinan Mustahiq Zakat Fitrah Perspektif Keadilan Dan Budaya - Ismaulina Ismaulina; Kherlina Kherlina (ITB AAS INDONESIA Surakarta, 2023)
This study discusses the culture and concept of justice in the determination and distribution of zakat fitrah to Mustahik which is carried out evenly in the people of Gampong Blang Crum, Lhokseumawe City. This field research was conducted using data collection techniques by means of observation, interviews, documentation and literature related to zakat fitrah. The subjects of this study consisted of Gampong Imum, Amil, Tuha Phet and Mustahiq which are in Gampong Blang Crum. The findings show that the determination of mustahiq zakat fitrah in Gampong Blang Crum, Lhokseumawe City, is contrary to the Koran. This is evidenced by the distribution of zakat fitrah evenly to all people. According to the concept of justice in Islam, it is not appropriate because the distribution of zakat fitrah evenly reduces the rights of mustahik, especially the poor. Meanwhile, according to Gampong Blang Crum culture, the distribution of zakat fitrah must be given evenly because it has become a longstanding habit. this has happened from generation to generation, no one even knows when the distribution of zakat fitrah evenly began. This is done to avoid social jealousy among residents. The distribution of zakat fitrah to the entire community is carried out after the distribution of zakat fitrah to the 4 asnaf that has been determined by the village. this is considered very fair and feasible, but this is not in accordance with an Islamic economic perspective because the purpose of zakat fitrah is to meet the needs of the poor.